How to make agricultural extension demand-driven?: The case of India’s agricultural extension policy - Birner, Regina; Anderson, Jock R. (International Food Policy Research Institute, 2007)
Many countries have recognized the need to revive agricultural advisory or extension services (the terms are used interchangeably here) as a means of using agriculture as an engine of pro-poor growth; reaching marginalized, poor, and female farmers; and addressing new challenges, such as environmental degradation and climate change. In spite of ample experience with extension reform worldwide, identifying the reform options most likely to make extension more demand-driven remains a major challenge. The concept of demand-driven services implies making extension more responsive to the needs of all farmers, including women and those who are poor and marginalized. It also implies making extension more accountable to farmers and, as a consequence, more effective. This essay discusses various options for providing and financing agricultural advisory services, which involve the public and private sectors as well as a third sector comprising nongovernmental organizations and farmer-based organizations. We review the market and state failures, and the “community” failures (failures of non-governmental and farmer-based organizations) inherent in existing models of providing and financing agricultural extension services and then outline strategies to address those failures and make extension demand-driven. Then we examine India’s Policy Framework for Agricultural Extension, which has demand-driven extension as one of its major objectives, and review available survey information on the state of extension in India. We conclude that although the framework proposes a wide range of strategies to make agricultural extension demand-driven, it is less specific in addressing the challenges inherent in those strategies. Moreover, it remains unclear whether the strategies proposed in the framework will be able to address one of the major problems identified by farm household surveys: access to agricultural extension.